Pengaruh Needs For Achievement Dan Karakteristik Pribadi Terhadap Keinginan Berwirausaha: Stud i Pada Mahasiswa FE Untar - Setiawan, Fanny Andriani (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The purpose of this study was to analyze Effect Needs for Achievement and Personal Characteristics Ã‚Â Of Desire Entrepreneurship: Studies Ã‚Â in Ã‚Â FE Student UNTAR. TheÃ‚Â data used Ã‚Â in this Ã‚Â study is primary data obtained Ã‚Â from a questionnaire research instruments were given to FE students UNTAR. Of the 500 Ã‚Â questionnaires distributed, the number of questionnaires Ã‚Â returned and deserves to dioleha Ã‚Â of 420 questionnaires. Data using multiple regression analysis to answer the hypothesis peneilitian with the software Ã‚Â PASW Ã‚Â Statistics Ã‚Â 18 Ã‚Â andÃ‚Â Eviews Ã‚Â 6. This Ã‚Â research Ã‚Â was Ã‚Â carried Ã‚Â Faculty of Economics, University Ã‚Â of Tarumanagara, Ã‚Â with the object Ã‚Â of study is Ã‚Â a student. Ã‚Â This study uses survey research with primary data collection using questionnaires. The selection Ã‚Â of samples Ã‚Â tested Ã‚Â in Ã‚Â this Ã‚Â study Ã‚Â usingÃ‚Â purposive Ã‚Â samplingÃ‚Â method, Ã‚Â 420 respondents was selected as the study sample. The results of this study were (I) Needs for achievement has a positive effect on the willingness of students to entrepreneurship, (2) Ã‚Â Gender positive effect Ã‚Â on the willingness Ã‚Â of students to entrepreneurship, (3) Age does not affect the Ã‚Â desire of students to entrepreneurship,Ã‚Â and (4) work experience possessed FE students UNTAR not affect students for entrepreneurship.